2021
DOI: 10.1007/jhep03(2021)039
|View full text |Cite
|
Sign up to set email alerts
|

Complement to thermodynamics of dyonic Taub-NUT-AdS spacetime

Abstract: We examine the thermodynamics of Euclidean dyonic Taub-Nut/Bolt-AdS4 black holes for a variety of horizon geometries to understand how gauge field regularity conditions influence the thermodynamic relations. We find several distinct features that distinguish the NUT-charged case from its dyonic Reissner-Nordstrom counterpart. For the Nut solution, the gauge field vanishes at the horizon and so regularity is ensured. For the Bolt solution we find that the norm of the gauge field is required to vanish at the hor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Besides the (anti-)self dual Eguchi-Hanson instanton in the conformally invariant case, there is an additional Taub-NUT/Bolt-AdS solution with a weakened AdS asymptotics. This can be obtained by considering the line element (21) as a metric ansatz and noticing that field equations in the conformally invariant case are solved by…”
Section: B Taub-nutmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the (anti-)self dual Eguchi-Hanson instanton in the conformally invariant case, there is an additional Taub-NUT/Bolt-AdS solution with a weakened AdS asymptotics. This can be obtained by considering the line element (21) as a metric ansatz and noticing that field equations in the conformally invariant case are solved by…”
Section: B Taub-nutmentioning
confidence: 99%
“…This solution is usually interpreted as a gravitational dyon since the NUT charge plays the role of a gravitomagnetic monopole, sourcing the magnetic part of the Weyl tensor [16][17][18][19]. In presence of Maxwell fields, the first charged Taub-NUT solution was obtained by Brill in [20] and different aspects of their thermodynamics have been recently studied [21,22]. 1 Holographic aspects of rotating Taub-NUT-AdS spaces have been studied through the Kerr/CFT correspondence [27][28][29][30] and it has been demonstrated that this solution describes holographic fluids with nontrivial vorticity [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Thermodynamics of the black hole with NUT charge have been studied recently in [25][26][27][28][29][30][31], especially in [7] for the Taub-NUT solution in Einstein case with conformal electrodynamics, which are main references for our study here. The event horizon of the NUTty dyon black hole generated by the Killing vector ξ = ∂ t is…”
Section: B Cohomogeneity Thermodynamicsmentioning
confidence: 99%
“…This solution is usually interpreted as a gravitational dyon since the NUT charge plays the role of a gravitomagnetic monopole, sourcing the magnetic part of the Weyl tensor [16][17][18][19]. In presence of Maxwell fields, the first charged Taub-NUT JHEP05(2022)110 solution was obtained by Brill in [20] and different aspects of their thermodynamics have been recently studied [21,22]. 1 Holographic aspects of rotating Taub-NUT-AdS spaces have been studied through the Kerr/CFT correspondence [27][28][29][30] and it has been demonstrated that this solution describes holographic fluids with nontrivial vorticity [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%